Development of LED-based pacing running system - Muhammad Adam Hamizan, Zainuddin; Muhammad Haniff, Gusrial; Nur Aqilah, Othman; Hamzah, Ahmad; Norhidayah, Mohamad Yatim (Springer, 2024)
This project aims to enhance running training methodologies by introducing a pacing system integrated with light-emitting diodes (LEDs). Traditionally, athletes manually determine their running pace, but the inherent risk of human errors limits the effectiveness of such approaches. Recognizing the critical role of a healthy pace in influencing an athlete’s productivity, endurance, and overall performance, a more precise strategy is imperative. This paper presents the development of an LED-based running pace system, designed to control and monitor the desired pace effectively. The system utilizes MIT App Inventor and an Xtensa microprocessor, implemented on an ESP32 microcontroller development board, chosen for its convenience, user-friendliness, and cost-effectiveness. The accompanying application provides real-time feedback and adjustable features, enabling athletes to progressively enhance their running performance. The testing results affirm the practicality and suitability of the proposed method for real-world applications.